33 Entropic model for real-time dose calculation. (December 2018) - Birindelli, G.; Feugeas, J.L.; Dubroca, B.; Caron, J.; Kantor, G.; Page, J.; Pichard, T.; Tikhonchuk, V.; Nicolaï, P.
Abstract : Introduction: This work proposes a completely new Grid-Based Boltzmann Solver (GBBS) developed for the transport and energy deposition by energetic particles. Its entropic closure and mathematical formulation allow our entropic model to calculate the delivered dose with an accuracy comparable to Monte Carlo (MC) codes with a computational time that is reduced to the order of few seconds without any special processing power requirement. Methods: In contrast to discrete ordinates angular discretization methods, such as Acuros®, our method is based on a reduced number of moment equations closed with Boltzmann's H-theorem. Keeping a good accuracy of calculations, the algorithm can simulate different treatment techniques such as the external radiotherapy even in presence of magnetic field[1, 2] (e.g., MRI-guided radiotherapy), brachytherapy or intra-operative radiation therapy. The first validation step consists in simulating dose distributions in complex numerical phantoms including a large number of heterogeneity shapes such as bone, lung and air. For both brachytherapy and external beam radiotherapy, simulations based on CT scan, using the real phase-space of the source, have been performed. The entropic model is validated by a direct comparison with the reference MC code PENELOPE. Results: The code is capable of calculating 3D dose distributions with 1 mm 3 voxels without statistical uncertainties in few seconds instead of several minutes like PENELOPE. In brachytherapy applications the dose distributions significantly differ from those calculated with the TG-43 approximations, thanks to its capability to account for inhomogeneities and strong density gradients. Moreover, for both applications the code shows an excellent agreement with PENELOPE within the 1%/1 mm gamma-index criterion. Conclusions: In the comparison with the MC results the excellent accuracy of the model is demonstrated. Thanks to its reduced computational time and its accuracy, this model is a promising candidate to become a real-time dose calculation algorithm.